The impact of downsizing on organizational commitment: A review of literature - Rosmaria, Jaffar @ Harun; Noor Aina Amirah, Mohd Noor; Alhamad Amal, Hmeidan Ghammar (2017)
PURPOSE AND BACKGROUND Workforce downsizing has become a popular human resource practice by management. Many business units have used different downsizing plans to restructure business units and develop products with lower cost. The impact of downsizing on survived employees affected their commitment significantly. This study aims to gives a better understanding of the effects of downsizing on organizational commitment of employees those survived from layoff after downsizing. This study also aims to provide better understanding of the relationship between these two variables, particularly the impact of downsizing on the commitment of employees after the downsizing and reduction of employees. METHODOLOGY This is accomplished by systematically analysing and combining the findings of independent studies through the analysis and evaluation. This research investigates the variables and relationships between variables which represent effects of downsizing on the survivors. The individual downsizing studies are the sources of the variables used to measure organizational commitment prevalent among downsizing survivors. The paper is based on secondary data like books, journals, articles, reports and websites. FINDINGS The finding of this study indicates that employees will feel unsettled during downsizing process and this feeling affect the behavior of employees inside their organization. Besides, only accepting loss of morale as an inevitable consequence may affect the organizational commitment of employees; also undermine the productivity. It is recommended that downsizing manager must ensure that survived employees from layoff should sustain loyalty and commitment towards their organization; otherwise there will be a negative impact on their organizational commitment. CONCLUSION This study concludes that employees will feel unsettled during downsizing and this feeling affect the behaviour of employees inside their organization. However, just accepting loss of morale as an inevitable consequence may affect the organizational commitment of employees; also undermine the very productivity gains intended by the change. The organization may lose a significant part of the human capital after the process of downsizing because of low attitude among survived employees which affect their commitment negatively.